MANAJEMEN SUMBER DAYA MANUSIA DALAM MEWUJUDKAN PEMBELAJARAN BERKUALITAS DI MADRASAH IBTIDAIYAH (MI) MA’ARIF NU 1 TUNJUNGMULI - ,, Fadlun (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2024)
This research aims to describe the planning, organization, implementation and control of human resources in realizing quality learning at the MI Ma’arif NU 1 Tunjungmuli. The approach used in this research is descriptive qualitative. The research location is at the MI Ma’arif NU 1 Tunjungmuli. In this research, the research subjects were the foundation chairs, boarding school leaders, all teachers, and madrasa committees. Research data was collected through in-depth interviews, participant observation, and document analysis. This research data was analyzed using interactive analysis techniques developed by Miles & Huberman, namely: data reduction, data presentation, and drawing conclusions. The results of the research show: (1) human resource planning in realizing quality learning at MI Ma’arif NU 1 Tunjungmuli is carried out at the beginning of every year, always making a list of educators for the students; (2) organizing human resources in realizing quality learning at MI Ma’arif NU 1 Tunjungmuli is carried out by holding meetings with educators, without any educational organization; (3) the implementation of human resources in realizing quality learning at MI Ma’arif NU 1 Tunjungmuli has gone well because it is a routine; and (4) control of human resources in realizing quality learning at MI Ma’arif NU 1 Tunjungmuli can be said to be quite good, control is also carried out by evaluating the human resources of the madrasa.